Stone Mineral Salt Solution As A Potential Nutrient For Biosurfactant And Biosolvent Production On Meor Application - Devitra Saka Rani; Sri Kadarwati (Testing Center for Oil and Gas LEMIGAS, 2009)
Bioproduct from microbial enzymatic activities such as biosurfactant, bioacid, biosolvent, and biopolimer is a useful product in improving oil recovery. The nutrient factors such as the difference and variation of the nutrient, influence microbial growth and enzymatic activities. The objective of this study is to examine the feasibility of Stone Medium Salt Solution (SMSS) as a potential nutrient for biosurfactant and biosolvent production on MEOR application. In the tube test, microbial mixed culture and 3 asphaltic crude oils, tested as C1, C2, and C3, were examined in 0%, 25%, 75%, and 100% SMSS concentrations. The microbial activities were determined by pH, viscosity, and interfacial tension measurements under microaerophilic and aerophilic conditions at 0-day and 7-day incubations. The Microbial Core Flooding (MCF) experiment was measured to observe in field application. The microbial consortia in all crudes had good growth using 100 % SMSS medium. After 7 days, the population increased in both microaerophilic and aerophilic conditions. The interfacial tension and viscosity of all crudes decreased except the viscosity of C1 in microaerophilic condition. The highest decrease occurred in C2 crude, which reduced 51% of interfacial tension and 58.73% of viscosity. Although the result of MCF experiment showed insignificant recovery (only 1.63% from Original Oil in Place), this study proves that SMSS nutrient can be applied in MEOR research by ex situ biosurfactant and biosolvent production for enhancing oil recovery.